Are We Ready For The Paradigm Shift In The Health Care System Of Pakistan? - Inayat H. Thaver; Nadia Khalid (Journal of Bahria University Medical and Dental College, 2021)
Pakistan’s health care indicators and accomplishment of its national as well international goals/targets though improving but are lagging the expected achievements1. The country is at a crossroads of having the demographic as well the epidemiologic transitions; besides these, social as well as mental issues are also increasing2. There is also a challenge of urbanization3 with its consequent flourishing of squatter settlements adding to burden on the health system.